Pathogen-induced activation of disease-suppressive functions in the endophytic root microbiome - Carrion, Víctor J; Perez-Jaramillo, Juan E; Cordovez, Viviane; Tracanna, Vittorio; De Hollander, Mattias; Ruiz-Buck, Daniel; Mendes, Lucas W; Van Ljcken, Wilfred F.J.; Gomez-Exposito, Ruth; S. Elsayed, Somayah; Mohanraju, Prarthana; Arifah, Adini; et al. (Science, 2019)
Microorganisms living inside plants can promote plant growth and health, but their genomic and functional diversity remain largely elusive. Here, metagenomics and network inference show that fungal infection of plant roots enriched for Chitinophagaceae and Flavobacteriaceae in the root endosphere and for chitinase genes and various unknown biosynthetic gene clusters encoding the production of nonribosomal peptide synthetases (NRPSs) and polyketide synthases (PKSs). After strain-level genome reconstruction, a consortium of Chitinophaga and Flavobacterium was designed that consistently suppressed fungal root disease. Site-directed mutagenesis then revealed that a previously unidentified NRPS-PKS gene cluster from Flavobacterium was essential for disease suppression by the endophytic consortium. Our results highlight that endophytic root microbiomes harbor a wealth of as yet unknown functional traits that, in concert, can protect the plant inside out
Keywords: Plantas - Microbiología; Disease Suppression; Fungal Pathogens; Chitinophagaceae; Flavobacteriaceae; Endophytic Microbiome; Biosynthetic Gene Clusters (BGCs)